Impact of time spent in parents-children communication on children misconduct - Kamaruddin, Nurani; Omar, Siti Zobidah; Hassan, Salleh; Abu Hassan, Musa; Che Mee, Arnida Ayu; D’Silva, Jeffrey Lawrence (Science Publications, 2012)
Communication is a must and family communication enhances family ties. This study is design to discover whether quantity of time spent between parents and children have a direct impact on children misconduct activities. This is a quantitative study using a survey questionnaire. Data were gathered from 1163 respondents which comprised of 641 secondary school children and 522 parents and were analyzed using SPSS software. The data collection process took three months to be completed. The outcome showed that the children perceive the amount of time spent with their parents does have an impact towards their misconduct activities. However, it was not the same for the parents. It seems that parents did not perceive that the amount spent for communicating with their children will affect their children’s misconduct activities. Parents should pay more attention to the time that they spent with their children as their children value the time that they spent with their parents’. It is crucial for parents to allocate some time in their hectic schedule to communicate with the children so that the children would not feel neglected and left out by their own parents thus making them prone to unhealthy activities.